2004
DOI: 10.1017/s1366728904001610
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinguistic influence at the syntax–pragmatics interface: Subjects and objects in English–Italian bilingual and monolingual acquisition

Abstract: The findings from a number of recent studies indicate that, even in cases of successful bilingual first language acquisition, the possibility remains of a certain degree of crosslinguistic influence when the choice between syntactic options is affected by discourse pragmatics. In this study we focussed on the use of referring expressions, prime candidates to test the interaction between syntax and pragmatics, and we compared the distribution of subjects and objects in the Italian and English of a bilingual chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
269
3
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(325 citation statements)
references
References 37 publications
19
269
3
17
Order By: Relevance
“…Other studies on the use of pronouns by EnglishItalian bilinguals, such as Serratrice, Sorace, and Paoli (2004) and Sorace, Serratrice, Filiaci, and Baldo (2009), concern children. These studies demonstrated two important points.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies on the use of pronouns by EnglishItalian bilinguals, such as Serratrice, Sorace, and Paoli (2004) and Sorace, Serratrice, Filiaci, and Baldo (2009), concern children. These studies demonstrated two important points.…”
Section: Introductionmentioning
confidence: 99%
“…The coordination of syntactic and pragmatic knowledge is a demanding task for young children in general (Avrutin 1999), and even more so in the case of bilingual children since they have to evaluate competing solutions to the syntax-pragmatics problem from two different languages. For the null-subject property, Serratrice et al (2004) predict that cross-linguistic influence will affect Italian, the more complex language. Cross-linguistic influence caused by processing limitations will lead to delay in the language whose processing is more complex.…”
Section: Delay Exceeding Monolingual Limits Due To Processing Limitatmentioning
confidence: 99%
“…That the delay effects are caused by processing complexity and not by linguistic complexity can be tested, since both views make different predictions for the acquisition process. According to Serratrice et al (2004), the presence and direction of the influence is a question of more-or-less constrained. In the case of null-subjects, the combination French-Italian should be as problematic as the combination GermanItalian or English-Italian.…”
Section: Delay Exceeding Monolingual Limits Due To Processing Limitatmentioning
confidence: 99%
“…In particular, early and late bilinguals (heritage speakers and L2 learners alike) have been reported to display deficits in the domain of inflectional morphology and narrow syntax, and both groups also seem to have difficulties with discourse-level phenomena. The former problem is manifested in errors or non-target-like performance with case, gender, agreement, verbal aspect, and long-distance dependencies (Benmamoun, Montrul, & Polinsky, 2010;Benmamoun, Montrul, & Polinsky, 2013a, b;Hawkins & Hattori, 2006;Montrul, 2002Montrul, , 2005Montrul, Foote, & Perpiñán, 2008;Polinsky, 1997Polinsky, , 2006Polinsky, , 2008aPolinsky, , b, 2011White, 2003), and the latter problem involves infelicitous linguistic choices in contexts that require discourse tracking or external pragmatic knowledge to resolve apparent contextual optionality (Laleko, 2010;Laleko & Polinsky, 2013;Montrul, 2004;Serratrice, Sorace, & Paoli, 2004;Sorace, 2011;Sorace, Serratrice, Filiaci, & Baldo, 2009). marking, and phenomena governed by external pragmatic conditions, e.g., topicalization and pronominal anaphora (Sorace, 2011 and references therein).…”
Section: Interfaces: the Integration Problemmentioning
confidence: 99%